2012
DOI: 10.3390/medicina48100079
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Self-Help Groups and Psychotherapy: Self-Assessment of Patients With Substance Use Disorders

Abstract: Background and Objective. The basis of substance use disorders (SUD) is formed with regard to biopsychosocial aspects. By following the SUD biological model exclusively, the effectiveness of treatment is limited since all the formation aspects of SUD are not taken into account. By using the psychosocial model, however, the understanding and treatment of a substance use illness becomes enhanced and is more effective. A key role in this model is played by self-help groups and psychotherapy. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, self-stigma can be reduced by attending a self-help group. In addition, it has been shown that outpatients with SUDs who attended a self-help group and also received psychotherapy had increased employment opportunities and an improved prognosis [ 41 ]. Although, for the sample in this study, there were no significant differences in how long participants had been attending a self-help group or in how many sessions they attended that affected acquired resilience and relapse risk; it appeared that attendance had a positive effect on self-esteem and self-efficacy and increased the chances of employment.…”
Section: Discussionmentioning
confidence: 99%
“…However, self-stigma can be reduced by attending a self-help group. In addition, it has been shown that outpatients with SUDs who attended a self-help group and also received psychotherapy had increased employment opportunities and an improved prognosis [ 41 ]. Although, for the sample in this study, there were no significant differences in how long participants had been attending a self-help group or in how many sessions they attended that affected acquired resilience and relapse risk; it appeared that attendance had a positive effect on self-esteem and self-efficacy and increased the chances of employment.…”
Section: Discussionmentioning
confidence: 99%
“…A larger effect was found at post-intervention through guided intervention ( g = 0.69) compared to self-help ( g = 0.21) in insomnia. It is possible that the absence of direct contact with a professional made it easier to stop treatment because there was less personal relationship pressure to continue with the intervention (Sudraba, Millere, & Rancans, 2012). The ES of QoL obtained at post-treatment with intervention-delivered face to face was numerically larger ( g = 0.71) than treatments that were delivered by other means (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, the efficacy associated with self-help groups and psy- chotherapy was explored in a group of 200 outpatients (28.5% attended self-help groups and 14.5% participated in group therapy). The results indicated that 1-month abstinence was 19.3%; 6-month abstinence was 22.8%; and 1-year or longer abstinence was 43.9% [5].…”
Section: Introductionmentioning
confidence: 95%